The value of research in the humanities - Quiroz Ávila, Ruben (2022)
There is unequal competition in the race for scientific publications. Even beyond the still erroneously valid neopositivist concept that equates the scientific to the exclusive and exclusive scientific production of the basic sciences, minimizing all humanistic production. To do this, they have set up a control apparatus of the organizations that are defining both the policies and their execution. The habitual system of those of us dedicated to the humanities is punished by not recognizing the diverse forms that our intellectual production adopts as a community of researchers in the human sciences.